Advances in Therapeutic Approaches to Extend Healthspan: a perspective from the 2nd Scripps Symposium on the Biology of Aging. Issue 4 (6th June 2017) - Robbins, Paul D.; Niedernhofer, Laura J.
Summary: The 2 nd Scripps Florida Symposium on The Biology of Aging entitled 'Advances in Therapeutic Approaches to Extend Healthspan' was held on January 22 nd –25 th, 2017 at The Scripps Research Institute in Jupiter, Florida. The meeting highlighted a variety of therapeutic approaches in animal models of aging that either are or soon will be in clinic trials. For example, drugs targeting senescent cells, metformin, rapalogs, NAD precursors, young plasma, mitochondrial‐targeted free radical scavengers, stem cells, and stem cell factors all have shown significant preclinical efficacy. This perspective, based on presentations and discussions at the symposium, outlines the current and future state of development of therapeutic approaches to extend human healthspan.